Performance and microbial response of suspended carrier-enhanced MBR treating tungsten smelting ammonia-nitrogen wastewater - Duliang Huang; Lin Huang; Jinmao Ye; Yu Zhang; Qingqing Yang; Changming Zhong (Journal of Environmental Chemical Engineering, 2026)

Partial nitrification-denitrification strategies with different sludge sources and their impact on membrane fouling behavior - Duliang Huang; Qingqing Yang; Lin Huang; Jinmao Ye; Yu Zhang; Changming Zhong (Journal of Environmental Management, 2026)

Tuning Fe-P covalency via regenerative phosphorus vacancies for efficient aqueous cyclohexanone degradation - Han Feng; Zhengyi Lu; Ming Chen; Changming Zhong; Yongquan Wang; Rong Lin; Wenfeng Xu; Junming Hong (Environmental Research, 2026)

Mean-State Arctic Sea Ice Transitions During 1979–2024 and the Underlying Physical Processes - Xia Lin; Yingrui Zhu; Weijia Li; Meibing Jin; Jingyi Huang; Xiuhao Guo; Xiaochun Wang; Jianfen Wei; Zhitong Lai; Changming Dong (Journal of Marine Science and Engineering, 2025)
Amplified Arctic warming has led to a pervasive decline in sea ice cover over recent decades; yet, the pattern and governing mechanisms of sea ice concentration (SIC) state transitions remain unclear. This study reveals pronounced regional contrasts in mean-state SIC during the transition from 1979–2006 to 2007–2024, concurrent with a reduction in the sea ice extent over the same period. The September-mean sea ice in the 70° N–80° N Arctic belt retreated significantly from 1979–2006 to 2007–2024, while the Barents and Greenland Seas exhibited persistent ice loss in March. Enhanced ice-albedo feedback, together with concurrent rises in the 2 m air temperature and sea surface temperature, dominate these ice loss processes. Dynamical processes exert distinct regulatory roles in September and March. The strengthened Beaufort High induces sea ice convergence to partially offset the September thermodynamically driven ice loss, while the positive-phase Arctic Dipole in March amplifies the transpolar airflow and winds over the Greenland and Barents Seas and triggers rapid sea ice export and significant loss in these regions. These findings underscore the spatial heterogeneity of Arctic SIC transitions and highlight the complex interplay of thermodynamic and dynamic processes shaping them.

Identification of CaMATE genes family in pepper and functional characterization of CaMATE27 in capsaicin accumulation - Liuying Fei; Rahat Sharif; Wanming Yan; Lin Chen; Yi Liao; Zhangsheng Zhu; Guoju Chen; Changming Chen (Plant Science, 2025)

Application of Large-Scale Rotating Platforms in the Study of Complex Oceanic Dynamic Processes - Xiaojie Lu; Guoqing Han; Yifan Lin; Qian Cao; Zhiwei You; Jingyuan Xue; Xinyuan Zhang; Changming Dong (Journal of Marine Science and Engineering, 2025)
As the core components of geophysical dynamic system, oceans and atmospheres are dominated by the Coriolis force, which governs complex dynamic phenomena such as internal waves, gravity currents, vortices, and others involving multi-scale spatiotemporal coupling. Due to the limitations of in situ observations, large-scale rotating tanks have emerged as critical experimental platforms for simulating Earth’s rotational effects. This review summarizes recent advancements in rotating tank applications for studying oceanic flow phenomena, including mesoscale eddies, internal waves, Ekman flows, Rossby waves, gravity currents, and bottom boundary layer dynamics. Advanced measurement techniques, such as particle image velocimetry (PIV) and planar laser-induced fluorescence (PLIF), have enabled quantitative analyses of internal wave breaking-induced mixing and refined investigations of vortex merging dynamics. The findings demonstrate that large-scale rotating tanks provide a controllable experimental framework for unraveling the physical essence of geophysical fluid motions. Such laboratory experimental endeavors in a rotating tank can be applied to more extensive scientific topics, in which the rotation and stratification play important roles, offering crucial support for climate model parameterization and coupled ocean–land–atmosphere mechanisms.

Effect of free ammonia control strategy on partial nitrification-denitrification in MBR reactor under low C/N conditions: Performance, SMP and EPS, and microbial community - Yu Zhang; Xihui Fang; Jinmao Ye; Lin Huang; Changming Zhong (Journal of Environmental Chemical Engineering, 2025)

Detection of three-dimensional structures of oceanic eddies using artificial intelligence - Guangjun Xu; Wenhong Xie; Xiayan Lin; Yu Liu; Renlong Hang; Wenjin Sun; Dazhao Liu; Changming Dong (Ocean Modelling, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Design and Optimization of a New Type of Magnetic Suspension Vibration Absorber for Marine Engineering - Changming Dai; Zhengyuan Liu; Yu Wang; Xiang Lin; Hui Liu; Bo Zhou (Journal of Marine Science and Engineering, 2023)
The magnetic suspension damper, which is based on magnetic suspension technology, is receiving more and more attention from academics as active–passive hybrid damping technology develops. A new symmetric magnetic suspension structure is constructed in this study, and the accuracy of the simulation findings is confirmed by contrasting the output from finite element simulation with the theoretical formulations. On the basis of this, how the structure, size, and material of the electromagnet and armature affect the magnetic flux density, electromagnetic force, and suspension force is investigated. The structure optimization of the electromagnet and armature was performed in accordance with the simulation results, and a new symmetric magnetic suspension structure was produced. The results of the simulation demonstrate that DT4(electrical pure iron) is the ideal material for armatures and electromagnets. The reinforcing ring construction can be built up by the armature to increase suspension force. The suspension force output by the armature will be greatly increased when the size and placement of the reinforcing ring structure are right. The system stiffness adjustment range will expand at this point, enhancing the magnetic suspension damper’s functionality. This study offers novel perspectives for designing structures that reduce vibration and noise in various projects and serves as a guide to constructing magnetic suspension dampers.

Contribution from ancient subducted slab to the Emeishan Large Igneous Province: Constraints from the petrogenesis of mafic intrusions in the western Guangxi area, South China - Hao Lin; Xiangke Wu; Hongfeng Qin; Changming Li; Yukun Li; Huimin Su; David A. Holwell; Dongyang Zhang (Lithos, 2023)

Keywords Query of uncertain spatiotemporal data based on XML - Changming Xu; Lin Zhu; Luyi Bai; Juan He (Earth Science Informatics, 2023)

The effect of short-term air pollutants exposure on outpatient admission for blepharitis in Shanghai, China: a hospital-based study - Han Zhao; Tong Lin; Yun Yang; Changming Feng; Wushuang Wang; Lan Gong (Environmental Science and Pollution Research, 2023)

The simultaneous removal of NO and SO2 over MnO2 material via the multi-stage fluidized bed process at low temperatures - Changming Li; Xiaoling Zhang; Yunjia Li; Lixin Sun; Lin Huangfu; Jianling Li; Shiqiu Gao; Jian Yu (Fuel, 2023)

Integrated small RNA profiling and degradome analysis of Anthurium andraeanum cultivars with different-colored spathes - Fazhuang Lin; Shi-Peng Chen; Kuan-Hung Lin; Changming Chen; Fengqin Yao; Linshan Zhong; Weiting Chen; Yun-Wei Kuo (Journal of Plant Research, 2022)

Growth Promotion and Salt-Tolerance Improvement of Gerbera jamesonii by Root Colonization of Piriformospora indica - Weiting Chen; Fazhuang Lin; Kuan-Hung Lin; Changming Chen; Chaoshui Xia; Qiaoling Liao; Shi-Peng Chen; Yun-Wei Kuo (Journal of Plant Growth Regulation, 2022)

Three-dimensional properties of mesoscale cyclonic warm-core and anticyclonic cold-core eddies in the South China Sea - Wenjin Sun; Yu Liu; Gengxin Chen; Wei Tan; Xiayan Lin; Yuping Guan; Changming Dong (Acta Oceanologica Sinica, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

Recovery of Fe and Al from red mud by a novel fractional precipitation process - Fengqin Yu; Lin Huangfu; Chao Wang; Changming Li; Jian Yu; Wensong Li; Shiqiu Gao (Environmental Science and Pollution Research, 2020)

Electroacupuncture ameliorates learning and memory deficits via hippocampal 5-HT1A receptors and the PKA signaling pathway in rats with ischemic stroke - Zhifu Wang; Bingbing Lin; Weilin Liu; Hongwei Peng; Changming Song; Jia Huang; Zuanfang Li; Lidian Chen; Jing Tao (Metabolic Brain Disease, 2020)

The root transcriptome analyses of peanut wild species Arachis correntina (Burkart) Krapov. & W.C. Gregory and cultivated variety Xiaobaisha in response to benzoic acid and p-cumaric acid stress - Zhong Li; Faqian Xiong; Wenfeng Guo; Changming Mo; Haining Wu; Lin Du (Genetic Resources and Crop Evolution, 2020)

Development of an Improved Immersing Method to Enhance Microbial Induced Calcite Precipitation Treated Sandy Soil through Multiple Treatments in Low Cementation Media Concentration - Kejun Wen; Yang Li; Shihui Liu; Changming Bu; Lin Li (Geotechnical and Geological Engineering, 2019)

Cytosine Methylation Analysis of Pinus elliottii × Pinus caribaea var. hondurensis and Their Parental Lines - Yiliang Li; Fencheng Zhao; Xiaohui Yang; Suiying Zhong; Fuming Li; Changming Lin; Huishan Wu; Wenbing Guo; Fangyan Liao (Journal of Plant Growth Regulation, 2019)

Cross-shelf transport induced by coastal trapped waves along the coast of East China Sea - Lin Jiang; Changming Dong; Liping Yin (Journal of Oceanology and Limnology, 2018)

Estimating the minimum in-stream flow requirements via wetted perimeter method based on curvature and slope techniques - Suxia Liu; Xingguo Mo; Jun Xia; Changming Liu; Zhonghui Lin; Baohui Men; Lina Ji (Journal of Geographical Sciences, 2006)